The changing structure of farm household economy in Malay rice-growing villages - Terano, Rika; Fujimoto, Akimi (Universiti Putra Malaysia Press, 2015)
This study focuses on the structure of household expenditure in discovering the real condition of household economy in rice-growing villages. We identified actual expenses and detailed consumption items for basic subsistence at the household level in two villages. The expenditure function in the two villages indicates that the head of the household, on-farm income and off-farm income are major determinants influencing the expenditure patterns and items bought by the household. In Kg. HC off-farm income and remittances determine household expenditure rather than on-farm income. The results indicate a contrast in expenditure behaviour at the household level between the two villages, where off-farm income in Kg. HC was strongly related to household expenditure while in the case of Kg. PTBB the relationship was influenced by on-farm income.